Biosensing application of multiwall boron nitride nanotube‐based nanoresonator for detecting various viruses. Issue 5 (1st October 2015) - Trivedi, Sandesh; Kumar, Surinder; Sharma, Satish Chand; Harsha, Suraj Prakash
Abstract : This study explores the suitability of biosensors using multi‐walled boron nitride nanotubes (MW‐BNNTs) with virus/bacterium attached at the free end of cantilever through vibration analysis. Various viruses/bacteria having mass of the order of zeptogram level are considered for obtaining resonance frequencies of cantilevered triple‐walled boron nitride nanotube (TW‐BNNT) by means of a continuum mechanics‐based analytical approach. The simulation with various viruses/bacteria attached at the tip of cantilevered TW‐BNNT is carried out for different lengths. The finite element method simulated resonance frequency values are compared with results obtained from the analytical method by taking into account the effective wall thickness of tubes and van der Waals interaction between various BNNTs. A close proximity is observed between results obtained from the two approaches, which further confirms the validity of the proposed model. The obtained results suggest that shorter length TW‐BNNT is more sensitive for detecting viruses/bacteria having mass of zeptogram order.